Mentally tough athletes are more aware of unsupportive coaching behaviours: Perceptions of coach behaviour, motivational climate, and mental toughness in sport - Nicholls, A. R.; Morley, D.; Perry, J. L. (International Journal of Sports Science & Coaching, 2016)
In this study, we tested an a priori model that included coach behaviour, motivational climate, and mental toughness among 290 athletes. Structural equation modelling demonstrated that supportive coach behaviours were related to a task-involving climate, and that task-involving climates positively associated with mental toughness. The path between supportive coach behaviours and mental toughness was insignificant. When task-involving climate was taken into account, however, supportive coach behaviours were positively associated with task-involving climates, which in turn was positively associated with mental toughness. This study illustrates the importance of coach behaviour in relation to shaping the motivational climate, which in turn may impact on the development of mental toughness among athletes.